The reality of inter-studies and the obstacles to activating them in the College of Education at King Saud University from the point of view of postgraduate students at the college - Al Daoud, Badr Abdulaziz Saad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to diagnose the reality of activating intra-studies, and to reveal the obstacles to that in the College of Education at King Saud University from the point of view of postgraduate students in the colleges of education. The study reached (297) postgraduate students randomly, and the study concluded: The reality of inter-educational studies in the College of Education at King Saud University obtained a total average of (2.37 out of 5), that is, with a (weak) degree, while the obstacles to activating educational inter-studies in the college came With an average of (3.42 out of 5), that is, with a (significant) degree, and the results indicated that there were no statistically significant differences at the level of (α≤0.05) in the study sample’s opinions towards all its axes according to the variable difference (gender, specialization). The researcher recommended the need to adopt material and moral stimulation programs necessary to encourage researchers to conduct more inter-studies, and to adopt communication programs with individuals conducting inter-studies to find out the necessary needs for conducting these studies, and to work on finding a clear and specific mechanism that contributes to increasing the level of scientific communication between the humanities faculties, He also suggested conducting studies to activate inter-educational studies in the scientific and applied departments, and conducting a study by presenting a proposed vision to activate joint supervision in educational scientific theses in the light of some international experiences.